Peran Mahasiswa KKn Berbasis Masjid dalam Meningkatkan Literasi Keagamaan dan Sosial Masyarakat Desa Riak Siabun: Penelitian - Fatrica Syafri; Sulthan Muhammad Alfaris; Helmania Sara; Ina Rudila; Chici Rifka; Aldo Jeki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mosques have a strategic role not only as a place of worship, but also as a center for character formation, socio-cultural, and spirituality of the community. This study aims to examine the role of Community Service Program (KKN) students in optimizing the function of mosques as centers of religious and social literacy in Riak Siabun I Village, Seluma Regency. The method used is qualitative descriptive with a case study at the Baitur Rahman Mosque. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively. The results of the study indicate that KKN activities based on religious and social literacy are able to build religious awareness, communal moral ethics, and increase solidarity and cultural participation of the community. A participatory approach that is sensitive to local cultural values is the key to the success of the program. The role of students as facilitators bridges academic knowledge with the needs of the community, while strengthening the role of mosque youth as agents of social change. This study underlines the importance of integrating relational ethical values and participatory education in village community development by strengthening the role of mosques.